OTHR-43. Composition of cell-free miRNA in cerebrospinal fluid and plasma as a monitoring tool for pediatric brain tumors. (3rd June 2022) - Anne, Coyle; Hollawell, Madison; Rathi, Komal; Beck, Christopher; Choudhari, Namrata; Smith, Tiffany; Peter, Madsen; Storm, Phillip; Resnick, Adam; Foster, Jessica; Koptyra, Mateusz
Abstract: Current clinical management of pediatric brain tumor patients involves non-invasive imaging studies to monitor therapeutic response and tumor progression. However, results are often inconclusive and unable to capture biological changes that presage progression on imaging. Non-invasive diagnostics, also termed liquid biopsy, have emerged for detection of cell-free cancer material but there are no such standard, clinically defined biomarkers or methods for pediatric brain tumors. Circulating miRNA presents an attractive biomarker platform given its stability in bio-fluids, selective expression in tumors and release from tumor cells into the extracellular environment. Technology development has permitted high throughput analysis of material obtained from biofluids including plasma and cerebrospinal fluid (CSF). We performed miRNA profiling across a cohort of 54 pediatric brain tumors from different histologies (low grade glioma, ependymoma, germinoma, medulloblastoma, atypical teratoid rhabdoid tumor and high-grade glioma) using CSF (33) and plasma (53) with HTG EdgeSeq platform. CSF and plasma specimens clustered independently of each other providing separate biomarker platforms. Consensus clustering performed on CSF specimens revealed clusters correlated with disease severity (tumor grade). We identified miRNA targets closely correlated with tumor grade (p<0.001), tumor dissemination or metastases (p<0.001) and survival (p=0.001). Similarly in plasma, through consensus clustering we identified cohorts with correlation to tumor grade. While distinct from those identified in CSF, specific plasma miRNA also correlated with clinical (tumor grade; p<0.001, dissemination or metastasis; p=0.002) and demographic (gender; p=0.001) features. Independently, histology-specific miRNA signature was also identified for low grade glioma, medulloblastoma and germinoma in plasma and CSF. The results present differential expression of cell-free miRNAs in plasma and CSF as biomarkers associated with diverse clinical diagnostic and prognostic measures. Further utilization of this approach provides unique platforms (plasma and/or CSF) to inform liquid biopsy-based management in the clinical setting.